Relevance of early stretching in overhead athletes - Schwartz, C.; Tubez, F.; Croisier, J. L.; Denoël, V.; Brüls, O.; Forthomme, B. (ISBS Proceedings Archive (Michigan), 2017)
Overhead athletes often develop, over time, a tightness of the posterior structures of the shoulder, which may be associated with injuries. Ten symptomatic (with pain) and ten asymptomatic players with a tight shoulder were compared and the effect of a selfapplied stretching program was evaluated. Before and after the stretching program, pain and stiffness of the shoulder were evaluated. Our results demonstrate that risk factors for shoulder pain such as glenohumeral internal rotation deficit and total range of motion deficit may only be limited in symptomatic athletes. The mobility of the shoulder was significantly improved after the stretching program for both groups. Pain was reduced when present. Because of the limited differences between the symptomatic and asymptomatic athletes, clinicians may find it advantageous to initiate early prevention or rehabilitation programs.